1991
DOI: 10.1523/jneurosci.11-05-01375.1991
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine inhibits excitatory but not inhibitory synaptic transmission in the hippocampus

Abstract: We examined the effects of adenosine and baclofen on inhibitory (IPSC) and excitatory (EPSC) synaptic currents in dissociated rat hippocampal neurons. Adenosine dramatically reduced monosynaptic EPSCs but failed to diminish IPSCs. This selective effect on EPSCs is likely due to inhibition of excitatory transmitter release because adenosine did not directly alter any properties of postsynaptic neurons. Baclofen depressed both EPSCs and IPSCs to approximately the same extent. These experiments indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
78
1
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 21 publications
18
78
1
2
Order By: Relevance
“…In both control and IL-6-stimulated slices, the GABAergic current represented nearly 10% of the compound current, as assessed by the degree of inhibition by ionotropic glutamate receptor antagonists. Activation of adenosine A 1 receptors with CPA (5 nM) did not affect IPSCs (99.7 ± 5.9% of currents amplitude before CPA, n ¼ 3) recorded from control slices, which is in accordance with previous data showing the inability of A 1 receptors to modulate GABAergic transmission in mature hippocampus (Lambert and Teyler, 1991;Yoon and Rothman, 1991). In slices incubated with IL-6 (10 U/ml) for 45-8 h, CPA (5 nM) also did not induce significant modifications on IPSCs amplitudes (95.6±9.9% of currents amplitude before CPA, n ¼ 3, p40.05), indicating that IL-6 was unable to unmask a putative A 1 receptor-mediated action upon GABAergic transmission in the hippocampus.…”
Section: Resultssupporting
confidence: 92%
“…In both control and IL-6-stimulated slices, the GABAergic current represented nearly 10% of the compound current, as assessed by the degree of inhibition by ionotropic glutamate receptor antagonists. Activation of adenosine A 1 receptors with CPA (5 nM) did not affect IPSCs (99.7 ± 5.9% of currents amplitude before CPA, n ¼ 3) recorded from control slices, which is in accordance with previous data showing the inability of A 1 receptors to modulate GABAergic transmission in mature hippocampus (Lambert and Teyler, 1991;Yoon and Rothman, 1991). In slices incubated with IL-6 (10 U/ml) for 45-8 h, CPA (5 nM) also did not induce significant modifications on IPSCs amplitudes (95.6±9.9% of currents amplitude before CPA, n ¼ 3, p40.05), indicating that IL-6 was unable to unmask a putative A 1 receptor-mediated action upon GABAergic transmission in the hippocampus.…”
Section: Resultssupporting
confidence: 92%
“…3 B, D). This confirms that the adenosine A 1 receptor responsible for presynaptic inhibition is only present on glutamate-releasing terminals (Yoon and Rothman, 1991;Wu and Saggau, 1997). Like EPSCs, and unlike native IPSCs, postload IPSCs were strongly inhibited by Ado (0.17 Ϯ 0.02; n ϭ 7) (Fig.…”
Section: Gaba Is Released Onto Normal Gaba a Receptorssupporting
confidence: 72%
“…Recordings from hippocampal neurons have shown that exogenous adenosine does not affect the presynaptic release of GABA (Yoon and Rothman, 1991;Thompson et al, 1992). Whether adenosine contributes to the modulation of GABA A R signaling in the acute setting of a seizure remains unexplored.…”
Section: Introductionmentioning
confidence: 99%